EXPLORING THE LIVED EXPERIENCES AND COPING STRATEGIES OF INDIVIDUALS WITH OBSESSIVE-COMPULSIVE DISORDER (OCD) IN LAHORE, PAKISTAN: A QUALITATIVE STUDY - Babar Lal; Fatima Rafique; Zartash Umer; Afeefa Saeed; Dr Javeria Saleem; Dr Muhammad Navid Tahir (International Journal of Contemporary Issues in Social Sciences, 2023)
Obsessive-Compulsive Disorder (OCD) is a globally prevalent mental health condition, with cultural influences impacting diagnosis and treatment. Limited research in Lahore, Pakistan, necessitates an exploration of OCD experiences and coping mechanisms to enhance regional mental health support. This qualitative study conducted in-depth interviews with fourteen OCD-diagnosed individuals in Lahore’s tertiary care hospitals. Utilizing a purposive sampling technique, the interviews, conducted in Urdu, explored lived experiences, coping strategies, and associated challenges. Thematic analysis revealed diverse demographic profiles of individuals with obsessive-compulsive disorder (OCD), showcasing a balanced distribution of age and gender. Major themes included preoccupations with order and symmetry, compulsive checking, and varying degrees of obsession. Participants struggled with uncontrollable and intrusive thoughts, often stemming from personal experiences and internal overthinking tendencies. The impact of OCD on daily life was profound, leading to isolation, hopelessness, and even self-harm. Coping strategies ranged from distraction and spirituality to seeking professional help. Social support varied, with some individuals experiencing discrimination. This qualitative study provides valuable insights into obsessive-compulsive disorder (OCD) experiences, unveiling themes related to order and symmetry, compulsive checking, hygiene concerns, obsessive behaviors, and the severity of obsessive thoughts. It sheds light on the impact of OCD on patients, their families, and social dynamics, emphasizing the need for family interventions and increased awareness to mitigate discrimination. The findings underscore the necessity for improved support systems and culturally tailored mental health services. Future research should focus on longitudinal studies, cross-cultural comparisons, and clinical validation for more effective interventions and policies.